FINASTERIDE AS A TREATMENT FOR MALE ANDROGENETIC ALOPECIA - Ni Komang Tristiana Dewi; I Wyn. Sugiritama (Universitas Udayana, 2013)
Androgenetic alopecia (AGA) is a type of alopecia non sikatrik that most often occur, especially in men. AGA is hereditary baldness and form distinctive patterns. Causes related to AGA estimated serum androgen levels, especially 5-?-dehydrotestosterone (DHT), which can lead to miniaturization of the hair follicle. Finasteride is one of drugs that proven effective in treating hair loss caused by AGA. Finasteride is a 4-azasteroid components that are competitive and specific inhibitor of the enzyme 5-?-reductase type II, an enzyme that converts testosteron into intracellular DHT. By inhibiting the enzyme 5-?-reductase type II, conversion of testosteron to DHT inhibited, thereby causing a significant decrease in serum and tissue DHT concentrations. The use of finasteride 1 mg per day proven to effectively treat AGA in men.